PENGARUH KECUKUPAN ANGGARAN DAN PENGENDALIAN INTERN TERHADAP KINERJA MANAJERIAL SKPD KABUPATEN REJANG LEBONG DENGAN GAYA KEPEMIMPINAN SEBAGAI VARIABEL MODERATING - Aziza, Nurna; Robinson, Robinson; Meriana, Meriana (UNIB Press, 2015)
The study aims to examine and obtain empirical affect the budget suffecient and internal control influence on the performance of local goverment, as well as the moderating role of leadership style, and the relationship of budget suffecient and internal control on the managerial performance of local goverment. Collecting data using primary data collection, is the questionnaire by using purposive sampling method, 90 respondents were selected as a sample of this study. The analytical method used in this study is multiple linear regression analysis and moderated regression analysis (MRA). The result showed that the budget suffecient and intern controls proved positive and significant effect on performance of local Goverment. Leadership style is no moderating variables that can amplify the effect ofthe budget suffecient and internal control on managerial performance SKPD Rejang Lebong.